The space between : a Christian engagement with the built environment - Jacobsen, Eric O. (Grand Rapids, MI : Baker Academic, 2012)
"The entire material world can be divided between the natural environment and the built environment. Over the past forty years, the natural environment has received the greater share of attention of the two, but that is beginning to change. With a renewed interest in 'place' within various academic disciplines and the practical issues of rising fuel costs and scarcity of land, the built environment has emerged as a coherent and engaging subject for academic and popular consideration.While there is a growing body of work on the built environment, very little of it approaches the built environment from a distinctly Christian perspective. This major new work by Eric Jacobsen, author of the well-received Sidewalks in the Kingdom, represents a comprehensive and grounded approach. Jacobsen develops a framework for understanding the built environment and addresses timely and controversial topics such as gentrification, urban sprawl, and energy consumption. Employing tools from the field of theology and culture, he demonstrates how looking at the built environment through a theological lens provides a unique perspective on questions of beauty, justice, and human flourishing.The space between is embellished with plentiful photographs, illustrations, charts, and exercises and will be of interest to students in cultural hermeneutics, theology and culture, urban ministry, or New urbanism / built environment courses at the college and seminary level. Pastors, missionaries, church planters, and Christian professionals will also find it of interest" -- Publisher description.
Orientation -- Who are you? -- Where are you? -- What are you? -- When are you? -- Participation -- Family -- Politics -- Church -- Engagement -- Sustainable environment -- Loving place.
Includes bibliographical references and index.
Keywords: Christianity and culture; Architecture and religion; Religion and geography; Cities and towns -- Religious aspects -- Christianity